Bioinformatics analysis and experimental studies reveal KPNA2 as a novel biomarker of hepatocellular carcinoma progression and telomere maintenance - Ke Ding; Lei Liu; Wang Yong; Beicheng Sun; Wenjie Zhang (European Journal of Medical Research)
Abstract Background Telomere maintenance mechanisms (TMMs) play a distinct role in the initiation and progression of hepatocellular carcinoma (HCC). However, the prognostic relevance of telomere maintenance (TM)-related genes in HCC remains largely unclear. Methods We integrated expression profiles of TM-related genes and corresponding clinicopathological data from public databases. Univariate analyses were performed to identify prognostic genes, and Cytoscape software was used to validate hub genes within the TM-related network. A novel prognostic signature was then constructed using the LASSO Cox regression algorithm. Finally, in vitro experiments were conducted to explore the functional roles of the key hub gene KPNA2 in telomere maintenance, tumor growth, and metastasis in HCC. Results In this study, we identified 224 differentially expressed TM-related genes for the first time. Functional enrichment and pathway analyses revealed that these genes were highly involved in telomere-associated pathways, including cell proliferation and cellular senescence. Protein–protein interaction (PPI) analysis identified eight hub TM-related genes (RNASEH2A, KPNA2, AURKB, FOXM1, MKI67, RAD54L, PLK1, and KIF4A), all of which were positively correlated with telomere maintenance. Furthermore, a novel TM-related prognostic signature comprising seven genes (KPNA2, CACNA1B, IRAK1, CDCA8, RGMA, ETS2, and GNE) was developed using the LASSO Cox model. Notably, KPNA2 was identified as both a TM-related hub gene and a component of the prognostic signature. KPNA2 was found to be significantly upregulated in HCC and associated with poor clinical outcomes. Functional assays revealed that KPNA2 knockdown suppressed telomerase activity, inhibited tumor cell proliferation and metastasis, whereas its overexpression produced the opposite effects. Telomerase inhibition partially alleviated the inhibitory effect of KPNA2 overexpression on cell proliferation and migration. Conclusions This study identified eight TM-related hub genes with prognostic significance in HCC and established a novel TM-related gene signature. Furthermore, we validated KPNA2 as a key regulator of telomere maintenance and tumor progression in HCC, suggesting it as a potential therapeutic target for improving clinical management of HCC.